1991
DOI: 10.1289/ehp.94-1567945
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and developmental toxicity of toluene: a review.

Abstract: Toluene is a widely used industrial solvent, and humans may also have high exposures to toluene from the deliberate inhalation ("sniffing") of paint reducer, paint thinner, or paint for their narcotic effects. A number of case reports describe neonatal effects that have been attributed to toluene abuse during pregnancy. These effects may include intrauterine growth retardation, premature delivery, congenital malformations, and postnatal developmental retardation. The possibility of exposures to other fetotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 12 publications
0
42
0
1
Order By: Relevance
“…1930 Anophthalmia and microphthalmia are also associated with a wide range of genetic syndromes,31 both chromosomal and monogenic, and it is likely that when a genetic syndrome is not evident, genetic susceptibility through one or more genes nevertheless plays a part in the response to environmental exposure.…”
Section: Discussionmentioning
confidence: 99%
“…1930 Anophthalmia and microphthalmia are also associated with a wide range of genetic syndromes,31 both chromosomal and monogenic, and it is likely that when a genetic syndrome is not evident, genetic susceptibility through one or more genes nevertheless plays a part in the response to environmental exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that benzylmercapturic acid is a minor metabolite of toluene. Toluene is also a respiratory irritant and has been implicated in cardiac (e.g., cardiac dysrhythmias) and other effects including chromosomal aberrations, reproductive and developmental complications, dermal irritation, and metabolic acidosis (Donald, et al, 1991;Schmid, et al, 1985). Both urinary hippuric acid and ortho-creosol are considered indicators of toluene exposure, although toluene in the blood and end-expired air has also been used to monitor exposure levels.…”
Section: Metabolism Of Toluene and Associated Health Effectsmentioning
confidence: 99%
“…Along with benzene and xylenes, toluene forms the BTX family and counts for the major part of the industry's VOCs emissions. Once released in the atmosphere, toluene participates in the formation of photochemical smog and ozone by photochemical reactions but it can also impact human health since it has been recognized as potential CMR (Carcinogenic, Mutagenic or toxic to Reproduction), especially when mixed with benzene . Long‐ and short‐term threshold limit values (TLV) have been set up to protect workers, with respectively 20 and 100 ppm values for the European Union…”
Section: Introductionmentioning
confidence: 99%